Psychological arrangement and expectations of university students to start companies and the managerial role - Vicuña Peri, Luis (1998)
We worked with a students sample of the UNMSM in the quarter and fifth year of studies in different faculties. We wanted to clear the following questions: To belong to a given academic faculty influences on the arrangements and on the psychological expectations for starting business and to assume the managerial role? and also. Are differents the males of the women in the arrangements and psychological expectations for the start business and to assume the managerial role? The method to clear the formulated questions is descriptive comparative of exploratory type. For the data compilation were elaborated two questionnaires: the first on psychological arrangements for the companies starling and the managerial role, the second was a questionnaire of self perception and furthermore was used the scale M-L-1996 of motivation. The gathered data was submitted to the variance analysis of two factors. Upon concluding the analysis was found that there are meaningful differences in the motivation solely in different faculties and not thus by gender, where the affiliation motivation characterizes prioritarily to the sanmarquino student next to finish carrers. Finally 90 % of the examined express their will to start business wich 49 % is inclined for services company, 22% by selling companies and 19% by production companies. 10 % says not to be able to form companies.